Innovative aspects of micropropagation in olive - Micheli, Maurizio; Regni, Luca; De Carlo, Anna; Benelli, Carla; Silvestri, Cristian (Frontiers in Plant Science, 2025)
The olive tree is one of the most iconic species within the Mediterranean Sea Basin. Countries bordering this sea enjoy a favourable climate that contributes to high-quality agricultural production for numerous horticultural species. The quality of the propagation material is one of the most important factors in determining the value of the final product, regardless of the cultivation-model, climate, and soil characteristics. Therefore, it is crucial to ensure genetic and sanitary certainty of vegetal/propagation material, which can be achieved through nursery productions. These goals are based on efficient propagation systems and methods to obtain high-biological quality plants. Over the last four decades, the application of biotechnology has introduced significant changes in the sector of nursery production. The Authors in this chapter aimed to present through their personal experimental experiences the latest advances in in vitro techniques and technologies that are revolutionizing the field of olive tree nurseries. While some of these methods are currently being employed, others are still undergoing research and development. Experts in this field firmly believe that all these techniques hold great practical value and have immense potential for high-quality nursery production.